Family and personal history of cancer in the All of Us research program for precision medicine - Keeler Bruce, Lauryn; Paul, Paulina; Kim, Katherine K.; Kim, Jihoon; Keegan, Theresa H. M.; Hiatt, Robert A.; Ohno-Machado, Lucila (PloS one, 2023)
The All of Us ( AoU ) Research Program is making available one of the largest and most diverse collections of health data in the US to researchers. Using the All of Us database, we evaluated family and personal histories of five common types of cancer in 89,453 individuals, comparing these data to 24,305 participants from the 2015 National Health Interview Survey (NHIS). Comparing datasets, we found similar family cancer history (33%) rates, but higher personal cancer history in the AoU dataset (9.2% in AoU vs. 5.11% in NHIS), Methodological ( e . g . survey-versus telephone-based data collection) and demographic variability may explain these between-data differences, but more research is needed.